2020
DOI: 10.3389/fmicb.2020.01002
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Mobile Genetic Elements in the Mitogenomes of Closely Related Fusarium culmorum and F. graminearum sensu stricto Strains and Its Implication for Diagnostic Purposes

Abstract: Much of the mitogenome variation observed in fungal lineages seems driven by mobile genetic elements (MGEs), which have invaded their genomes throughout evolution. The variation in the distribution and nucleotide diversity of these elements appears to be the main distinction between different fungal taxa, making them promising candidates for diagnostic purposes. Fungi of the genus Fusarium display a high variation in MGE content, from MGE-poor (Fusarium oxysporum and Fusarium fujikuroi species complex) to MGE-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 73 publications
1
12
0
Order By: Relevance
“…In this study, we confirmed that the irregular distribution of MGEs does not follow divergence of cryptic species within the FGSC. This finding supports the hypothesis of low mobility of ancestrally acquired MGEs that are consequently shared by geographically diverse cryptic species ( Kulik et al, 2020b ). These ancestral elements may undergo changes throughout evolution, and assuming the lack of horizontal gene flow, these alternations should, at least in part, exhibit species-specific polymorphism.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In this study, we confirmed that the irregular distribution of MGEs does not follow divergence of cryptic species within the FGSC. This finding supports the hypothesis of low mobility of ancestrally acquired MGEs that are consequently shared by geographically diverse cryptic species ( Kulik et al, 2020b ). These ancestral elements may undergo changes throughout evolution, and assuming the lack of horizontal gene flow, these alternations should, at least in part, exhibit species-specific polymorphism.…”
Section: Discussionsupporting
confidence: 89%
“…Notably, variation in MGE content appears to be dependent on taxonomic sampling. This variation can be highly conserved, indicating a low mobility of ancestrally acquired MGEs ( Kulik et al, 2020b ). In contrast, more recent enrichment events result in increased mosaicism of MGE patterns that can be observed at the population level ( Wolters et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Linear versions have also been observed and some circular version could actually exist as linear concatemers generated by a rolling circle type DNA replication mechanism ( Bendich, 1993 ; Hausner, 2003 , 2012 ; Bullerwell and Lang, 2005 ; Baidyaroy et al, 2011 ; Valach et al, 2011 ; Chen and Clark-Walker, 2018 ). Mitochondrial genome architecture and size are highly variable among the fungi due to recombination events promoted by repeats and by the presence and activities of mobile elements such group I and group II introns and intron-encoded proteins (IEPs) ( Aguileta et al, 2014 ; Wu and Hao, 2014 , 2019 ; Franco et al, 2017 ; Repar and Warnecke, 2017 ; Deng et al, 2018 ; Stone et al, 2018 ; Zubaer et al, 2018 ; Kolesnikova et al, 2019 ; Kulik et al, 2020 ; Liu et al, 2020b ). Like other fungi, most of the mitogenome variation observed among the examined members of the Ophiostomatales is due to the absence and presence of introns.…”
Section: Discussionmentioning
confidence: 99%